Effects of variations in hysterectomy status on population coverage by cervical screening - Kerri Beckmann; Penny Iosifidis; Lesley Shorne; Sue Gilchrist; David Roder (Elsevier, 2003)
Objectives: To investigate geographic differences in hysterectomy rates and effects on estimated screening coverage in South Australia. Methods: Hysterectomy data from South Australian hospitals for 1992-2000 were used to calculate age‐specific hysterectomy rates for 20-69 year old women by residential subregion and postcode. Regional variations in rates were used to estimate variations in proportions of women with an intact uterus. Effects on estimates of screening coverage were investigated. Results: About 66% of South Australian women were estimated to have an intact uterus at 70 years of age, based on hysterectomy rates for 1992-2000. The proportion was smaller in lower than upper socio‐economic areas, and in country areas than the State capital (Adelaide). Estimates varied from 49% to 73% across 20 subregions. About 67% of 20-69 year olds with an intact uterus were estimated to have been screened in the 24‐month period from 2000 to 2001. Similar estimates applied to Adelaide and country areas, irrespective of whether adjustments were made for differences in hysterectomy rates. A lower screening coverage applied to lower than upper socio‐economic areas of Adelaide, irrespective of whether these adjustments were made. While adjusting for variations in hysterectomy rates generally had little effect on estimated screening coverage, there were notable exceptions. For example, in one subregion, coverage increased among 50-69 year olds from 53% to 66%. Conclusions: Adjustments for variations in hysterectomy rates can affect estimated screening coverage in some localities. Such adjustments should be undertaken to better define areas of under‐screening for targeting in screening promotion.